Radiation and magnetohydrodynamic effects on convective nanofluid past an inclined plate in the presence of a chemical reaction - Palani, Geetha; Arutchelvi, A. (Zielona Góra: Uniwersytet Zielonogórski)
This computational work explores the heat and mass transfer of copper water nanofluid flowing along an inclined plate with varying surface temperature and concentration in the presence of a magnetic field and radiation through a permeable medium. The dimensionless governing equations are solved numerically using an efficient finite-difference technique, which is fast convergent and unconditionally stable. The findings are reviewed and illustrated through graphs for pertinent parameters.
Keywords: finite difference; nanofluids; viscous dissipation; heat source; porous medium